(untitled) (Eastern Medical College Journal, 2026)
Background: Modern lifestyles in urban areas have been considered to be potentially responsible for the development of airway problems. One of the components of modern lifestyle is the intensive use of air conditioners (AC). Increased inhalation of cold dry air of air conditioner ultimately may cause alteration of pulmonary functions. The objective of this study was to assess the impact of air. Materials & Methods: This quasi-experimental study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram, during January 2019 to December 2019 in collaboration with Continental Group Private Limited, Chattogram and EPV (Energypac Power Venture) Chittagong Limited, Patiya, Chattogram. 35 apparently healthy adult males between the ages 20-45 years, working in air-conditioned environment was taken as case. 35 healthy age and sex matched subjects, working in non-air-conditioned environment were taken as control. This study was done to measure pulmonary function test parameters among healthy AC users, and they were compared with non-users of AC to see the effects of AC on lung functions. Lung function test parameters like FVC, FEV1, FEV1/FVC ratio, respiratory rate and SPO2 were measured by digital spirometer and pulse oximeter. Unpaired Student’s ‘t’ test and Chi-square test were done by using SPSS-25 for statistical analysis. Results: The mean value of FVC, FEV1 and SPO2 were significantly lowered in AC users; mean value of respiratory rate were significantly increased in AC users comparing with control. FEV1/FVC ratio was increased in AC users compared with control. Conclusion: The result of this study suggests that pulmonary function is significantly decreased after usage of air conditioner. Therefore, public awareness for proper maintenance of AC, periodic analysis of pulmonary functions, limited use of AC and regular respiratory exercise can be recommended for preserving respiratory efficiency. Eastern Med Coll J. July 2025; 10 (2): 132-136